Compliance of the UK Human Rights Act with the European Convention on Human Rights. Case in point: the UK AI surveillance system - Yenoyan, Liana (Riga Graduate School of Law, 2023)
This thesis addresses the significance of human rights in the United Kingdom. Due to the fact that the technology, notably Artificial Intelligence, is advancing at a lightning speed, at times it is hard to define the line between human rights and governmental power. The purpose of this thesis was to establish if the UK Artificial Intelligence Surveillance System goes against the law or complies with the European Convention on Human Rights. Following the analysis of various case studies and all available material, the author concluded that, despite the number of violations, the Human Rights Act is critical for maintaining the fundamental and inalienable rights granted to every individual. Any effort to change it or totally replace it with the newly proposed Bill of Rights Bill will damage the UK's international reputation and, eventually, cause legal uncertainty
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Human rights law; Artificial intelligence; The United Kingdom; Surveillance Systems